Analysis of socio-economic dynamics of the Azerbaijan regions - Babayev, Nusret S. (The journal of contemporary issues in business and government, 2021)
The regional circle's role is growing in the context of the collapse of centralized governance and liberalization of economic relations, and now several scientists and civil servants are actively implementing methods and tools to address pressing issues of sustainable development of the country and its regions. From this point of view, at a time when large-scale reforms are being carried out, it is named the state's regional economic policy and its regulatory and management mechanisms that set priority and long-term goals for the development of regions and their sectors, and their implementation is stimulated and ensured. The main task of achieving the strategic and current goals set by the regional policy at the modern stage of development is to achieve the development of various forms of economy and more efficient placement in the economic regions by using the productive capacity, natural-economic opportunities, local and foreign investment, scientific-technical and personnel potential of all economic regions of the country. The article analyzes the dynamics of socio-economic development in the regions in recent years and the factors that have changed the quantitative and qualitative changes in them. Indicators of the impact of the new economic and social facilities on the living standards of different economic regions and Baku city were also given, including the Theil index and Gini coefficient for economic regions. The article uses systematic analysis, scientific, logical summarization, economic classification, and other research methods. At the end of the analysis, the relevant findings were substantiated.